Exploring foreign language anxiety in higher education: Multifaceted insights into causes, impacts, and coping strategies - Osman Özdemir; Hümset Seçkin (Social Sciences and Humanities Open)
It is believed that high anxiety in foreign language learning can negatively affect learners' language learning processes and hinder the development of their language skills. Focusing specifically on the context of higher education, this study aims to examine in depth the perspectives of both first-year students and instructors on anxiety related to the productive skills of speaking and writing in English. Although previous studies have addressed language anxiety comprehensively, it is observed that there is very limited research that examines students' and instructors' perspectives on writing and speaking skills anxiety together. In this qualitative study, data were collected through semi-structured interviews with students and instructors in the Department of English Translation and Interpreting at Selcuk University. The data obtained from the interviews were analyzed in detail and meticulously through thematic analysis. The theoretical framework of the study consists of the literature on the origins, symptoms and consequences of language anxiety and the cumulative process of students' language learning experiences and instructors' language teaching experiences and observations. The findings show that the most common factors that increase students' speaking anxiety are fear of making pronunciation mistakes, speaking in front of others, lack of vocabulary knowledge, unwillingness to speak and lack of exposure to English. On the other hand, difficulty in organizing ideas, lack of vocabulary and grammatical knowledge, lack of specialized terminology knowledge and insufficient language proficiency increase writing anxiety the most. To cope with speaking anxiety, students suggested improving listening skills, improving grammatical knowledge and enough pronunciation practice, while instructors suggested giving positive feedback, praising accomplishments and pair work/groupwork activities. In order to cope with writing anxiety, students mostly suggested developing academic strategies, while instructors suggested developing language enhancement strategies. This study sheds light on the complex dimensions of English speaking and writing anxiety and offers practical suggestions for both language teachers and language learners to address this problem. The findings are considered to be instructive not only for language teaching practice but also for educational policy makers, practitioners and researchers.